2016
DOI: 10.1182/blood-2016-05-713545
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-4-hydroxylase 2 and 3 coregulate murine erythropoietin in brain pericytes

Abstract: A classic response to systemic hypoxia is the increased production of red blood cells due to hypoxia-inducible factor (HIF)-mediated induction of erythropoietin (EPO). EPO is a glycoprotein hormone that is essential for normal erythropoiesis and is predominantly synthesized by peritubular renal interstitial fibroblast-like cells, which express cellular markers characteristic of neuronal cells and pericytes. To investigate whether the ability to synthesize EPO is a general functional feature of pericytes, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 67 publications
1
60
1
1
Order By: Relevance
“…A compensatory mechanism by PHD3, which limits the HIF response as a consequence of a PHD2 knockout has been described in several cell and animal models. 21 , 28 , 29 , 30 This might explain why some phenotypes induced by a PHD2 knockout are more severe in combination with knocking out PHD3. A singular knockout of PHD3 alone, however, seems to reveal the PHD3 isoform-specific functions and might explain, why the phenotype observed in the PHD3 −/− compared to the WT mice are seen just in the ischemic legs in situ or under simulated ischemic conditions in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…A compensatory mechanism by PHD3, which limits the HIF response as a consequence of a PHD2 knockout has been described in several cell and animal models. 21 , 28 , 29 , 30 This might explain why some phenotypes induced by a PHD2 knockout are more severe in combination with knocking out PHD3. A singular knockout of PHD3 alone, however, seems to reveal the PHD3 isoform-specific functions and might explain, why the phenotype observed in the PHD3 −/− compared to the WT mice are seen just in the ischemic legs in situ or under simulated ischemic conditions in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has recently shown that renal EPC are derived from forkhead box D1‐expressing stroma, which surrounds the cap mesenchyme during kidney development and gives rise to essentially all nonendothelial renal interstitial cells including pericytes and perivascular fibroblasts, mesangial cells, and vascular smooth muscle cells. Interestingly, the ability to produce EPO is shared between brain and renal pericytes, which are both of neural crest origin . PHD2 is the main prolyl hydroxylase that controls HIF activity under normoxic conditions.…”
Section: The Phd/hif Axis In Erythropoiesis and Iron Metabolismmentioning
confidence: 99%
“…Interestingly, the ability to produce EPO is shared between brain and renal pericytes, which are both of neural crest origin. 38,40 PHD2 is the main prolyl hydroxylase that controls HIF activity under normoxic conditions. Its genetic inactivation in renal interstitial cells results in HIF-2 activation and EPO production in 40% of cortical and outer medullary renal interstitial cells leading to severe polycythemia.…”
Section: Oxygen-dependent Epo Production In the Kidneymentioning
confidence: 99%
“…HIF-P4H-2 (PHD2/EglN1) is the most abundant isoenzyme and the major one regulating HIFstability. In kidney, inactivation of HIF-P4H-2 was sufficient to induce EPO expression while in brain pericytes and hepatocytes it required simultaneous inactivation of HIF-P4Hs 2 and 3 or all HIF-P4Hs, respectively [57,108]. FIH (magenta), which shares the same reaction mechanism and cofactors with HIF-P4Hs but is less dependent on oxygen, hydroxylates an asparagine residue in HIF1/2α.…”
Section: Clinician's Corner Boxmentioning
confidence: 99%